Identification of Effective Components in Hospital Performance Assessment: A Qualitative Study - Roya Malekzadeh; Ghasem Abedi; Ghahraman Mahmoodi (Kerman University of Medical Sciences, 2021)
Introduction: An appropriate and applicable model of hospital performance assessment can potentially lead to accountability, quality of service, and patient satisfaction. The purpose of this study was to identify the effective factors on hospital performance assessment. Methods: In this qualitative study, in order to elucidate the experts' experiences of hospital performance assessment, based on purposive sampling, individual semi-structured interviews were conducted with 27 health services management professors, university and hospital managers, national accreditors, and the authorities in charge of quality improvement of hospitals in Mazandaran Province. Interviews were recorded, transcribed, codified, classified, and analyzed based on the conventional content analysis approach. Results: The participants' experiences indicated the need to take into account all dimensions influencing performance assessment as well as a balanced measurement of the structure, process, outcome, control, and context of the hospital that provides services. Totally, 5 main themes and 18 sub-themes were extracted from the data analysis. Conclusion: The results of this study indicated that a comprehensive performance assessment system needs to measure all dimensions of hospital performance. It is therefore recommended that in hospital performance assessment, in addition to traditional attention paid to resources and facilities, hospital processes, the outcomes of proper implementation of processes, control, and the context in which the hospital provides services also be taken into account.